Blow-up criteria for the generalized Degasperis–Procesi equation. Issue 13 (2nd September 2022) - Deng, Xijun
ABSTRACT: In this paper, we investigate the initial value problem of the generalized Degasperis–Procesi equation. We establish some new local-in-space blow-up criterion. Our results extend the corresponding results in the previous literature.